Exploring What Drives Undergraduates at Xihua University in Chengdu to Stick with Short Video Apps - Li, Siqi (Scholar: Human Sciences, 2025)
Purpose: This research paper investigates the factors impacting user continuance intention on short video applications among undergraduates from Xihua University in Chengdu, China. The conceptual framework proposed a causal relationship among information sharing, information seeking, social interaction, entertainment, facilitating condition, and satisfaction impacting continuance intention. Research design, data, and methodology: The researcher applied the quantitative method (n=500), distributing questionnaires to undergraduates from Xihua University. The sampling process involved multi-stage sampling, including judgmental sampling to select four majors’ undergraduates of Xihua University, followed by stratified random sampling to proportionately allocate the sample size across these four majors and conclude with convenience sampling for distributing the questionnaire. The Structural Equation Model (SEM) and Confirmatory Factor Analysis (CFA) were used for the data analysis, and they included model fit, reliability, and validity of the constructs. Results: The results explicated that continuance intention was significantly and directly impacted by information seeking, social interaction, entertainment, facilitating condition, and satisfaction. Satisfaction strongly impacts continuance intention, followed by entertainment, information seeking, facilitating conditions, and social interaction. Moreover, it is indirectly impacted by information sharing. Conclusions: Companies and developers are suggested to ensure that the attributes of information sharing, information seeking, entertainment, and social interaction are available when using the app, and the app offers diverse, engaging, and high-quality content to meet users’ viewing needs and interests.